Small airways pathology in idiopathic pulmonary fibrosis: a retrospective cohort study. Issue 6 (June 2020) - Verleden, Stijn E; Tanabe, Naoya; McDonough, John E; Vasilescu, Dragoş M; Xu, Feng; Wuyts, Wim A; Piloni, Davide; De Sadeleer, Laurens; Willems, Stijn; Mai, Cindy; Hostens, Jeroen; Cooper, Joel D; et al.
Summary: Background: The observation that patients with idiopathic pulmonary fibrosis (IPF) can have higher than normal expiratory flow rates at low lung volumes led to the conclusion that the airways are spared in IPF. This study aimed to re-examine the hypothesis that airways are spared in IPF using a multiresolution imaging protocol that combines multidetector CT (MDCT), with micro-CT and histology. Methods: This was a retrospective cohort study comparing explanted lungs from patients with severe IPF treated by lung transplantation with a cohort of unused donor (control) lungs. The donor control lungs had no known lung disease, comorbidities, or structural lung injury, and were deemed appropriate for transplantation on review of the clinical files. The diagnosis of IPF in the lungs from patients was established by a multidisciplinary consensus committee according to existing guidelines, and was confirmed by video-assisted thoracic surgical biopsy or by pathological examination of the contralateral lung. The control and IPF groups were matched for age, sex, height, and bodyweight. Samples of lung tissue were compared using the multiresolution imaging approach: a cascade of clinical MDCT, micro-CT, and histological imaging. We did two experiments: in experiment 1, all the lungs were randomly sampled; in experiment 2, samples were selected from regions of minimal and established fibrosis. The patients and donors were recruited from the Katholieke Universiteit Leuven (Leuven, Belgium) and the University of Pennsylvania Hospital (Philadelphia, PA, USA). The study took place at the Katholieke Universiteit Leuven, and the University of British Columbia (Vancouver, BC, Canada). Findings: Between Oct 5, 2009, and July 22, 2016, explanted lungs from patients with severe IPF (n=11), were compared with a cohort of unused donor (control) lungs (n=10), providing 240 samples of lung tissue for comparison using the multiresolution imaging approach. The MDCT specimen scans show that the number of visible airways located between the ninth generation (control 69 [SD 22] versus patients with IPF 105 [33], p=0·0023) and 14th generation (control 9 [6] versus patients with IPF 49 [28], p<0·0001) of airway branching are increased in patients with IPF, which we show by micro-CT is due to thickening of their walls and distortion of their lumens. The micro-CT analysis showed that compared with healthy (control) lung anatomy (mean 5·6 terminal bronchioles per mL [SD 1·6]), minimal fibrosis in IPF tissue was associated with a 57% loss of the terminal bronchioles (mean 2·4 terminal bronchioles per mL [SD 1·0]; p<0·0001), the appearance of fibroblastic foci, and infiltration of the tissue by inflammatory immune cells capable of forming lymphoid follicles. Established fibrosis in IPF tissue had a similar reduction (66%) in the number of terminal bronchioles (mean 1·9 terminal bronchioles per mL [SD 1·4]; p<0·0001) and was dominated by increased airspace size, Ashcroft fibrosis score, and volume fractions of tissue and collagen. Interpretation: Small airways disease is a feature of IPF, with significant loss of terminal bronchioles occuring within regions of minimal fibrosis. On the basis of these findings, we postulate that the small airways could become a potential therapeutic target in IPF. Funding: Katholieke Universiteit Leuven, US National Institutes of Health, BC Lung Association, and Genentech.